Proposta de localização de uma unidade de tratamento de óleo e gordura residual de fritura na cidade do Natal/RN para produção de biodiesel - Pinto, Janete Maria Barreto (2009)
This work addresses biodiesel by transesterification from the use of waste frying oil as a possible technological alternative for both reducing greenhouse gas emissions and by presenting themselves as an environmental call to designate a rational use of oil when no longer played in the environment to become renewable energy. It has proposed location of a residual oil and fat treatment plant to produce biodiesel, using models of Location and Routing for the improvement of routes. To achieve the goal, questionnaires were administered in establishments that use oil or vegetable fat in their productive activities in order to quantify the residue, to analyze actions and environmental perception of people who work directly with the residue on the destination you are being given to oil and fat used. It has indicated using of two single setup location, the method of Center of Gravity and the model of Ardalan, a geographical point that minimizes the costs of transporting waste to the treatment plant. Actions have been proposed for the improvement of collection routes this residue using the Routing Method of Scanning, as an illustration. The results demonstrated the lack of knowledge of the people who deal directly with large amounts of waste, on the environmental impacts caused by their incorrect disposal. The models used were uniform since point out to neighborhoods in similar regions. The neighborhoods of Lagoa Nova / Morro Branco (Ardalan) and Nova Descoberta (Center of Gravity) as ideal for the installation of treatment plant. However, it is suggested to be tested other models that take into account new variables than those used (supply of waste and the distance between points). The routing through the method of scanning has shown that it is possible, in a simple way to optimize routes in order to reduce distances and therefore the logistics costs in the collection of such waste. Introducing a route as a test to gather the twenty largest oil suppliers used in sample frying, using as a main factor time 8 hour of working shift every day